Avaliação do potecial químico e biológico de Tephrosia toxicaria Pers. (Fabaceae) - Vasconcelos, Jackson Nunes e (2010)
Tephrosia toxicaria Pers. (Fabaceae) popularly known as "timbó de caiena" is used as pesticide and fishing poison, because its activity icthyotoxic. This work reports the chemical study of T. toxicaria and its larvicidal and antioxidant activities evaluation. Phytochemical investigation led to the isolation of ten flavonoids (TTP-1 – luteolin, TTP-3 – 6a,12a-dehydro-a-toxicarol, TTP-4 – a-toxicarol, TTP-5 – obovatin, TTP-6 – deguelin, TTP-8 – villosinol, TTP-9 – 12a-hydroxy-a-toxicarol, TTP-10 – sumatrol, TTP-11–12a-hydroxyrotenone and TTP-12 – tephrosin) – eight of them rotenoids – one cromone (TTP-13 – 6,7-dimethoxychromone) and the mixture of steroids sitosterol and stigmasterol, in their simple forms and glycosylated. Antioxidant and larvicidal assays were performed with several extracts, partitions and with some of the secondary metabolities isolated. Due to the presence of rotenoids, compounds have been used to control in agricultural pest since the XIX century, the study of T. toxicaria was quite promising, with several active extracts, with activity comparable to that of rotenone, compound used as a positive test. Its antioxidant activity tests shown T. toxicaria as a potential source of these agents, probably due to the presence of flavonoids, compounds characteristic for presenting various types of biological activities. The substances were isolated and its structures determined by spectroscopic and spectrometric methods (IR, EM, 1H NMR and 13C NMR), including two-dimensional NMR (HMBC, HSQC and COSY) and by comparison with literature data.